2018
DOI: 10.1017/ice.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator Bundle Compliance and Risk of Ventilator-Associated Events

Abstract: OBJECTIVEVentilator bundles encompass practices that reduce the risk of ventilator complications, including ventilator-associated pneumonia. The impact of ventilator bundles on the risk of developing ventilator-associated events (VAEs) is unknown. We sought to determine whether decreased compliance to the ventilator bundle increases the risk for VAE development.DESIGNNested case-control study.SETTINGThis study was conducted at 6 adult intensive care units at an academic tertiary-care center in Tennessee.PATIEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 35 publications
1
48
0
1
Order By: Relevance
“…(weak recommendation, low quality of evidence) We recommend obtaining a lower respiratory tract sample (distal quantitative or proximal quantitative or qualitative culture) to focus and narrow the initial empiric antibiotic therapy. (strong recommendation, low quality of evidence) digestive decontamination may not be effective in ICUs with high baseline rates of antibiotic resistance, and subglottic secretion drainage may not shorten duration of mechanical ventilation or ICU length-of-stay as was once thought [91][92][93][94][95]. The practices most consistently associated with earlier extubation and/or lower mortality rates are those focused on limiting exposure to invasive mechanical ventilation by avoiding intubation and speeding extubation [96].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
See 1 more Smart Citation
“…(weak recommendation, low quality of evidence) We recommend obtaining a lower respiratory tract sample (distal quantitative or proximal quantitative or qualitative culture) to focus and narrow the initial empiric antibiotic therapy. (strong recommendation, low quality of evidence) digestive decontamination may not be effective in ICUs with high baseline rates of antibiotic resistance, and subglottic secretion drainage may not shorten duration of mechanical ventilation or ICU length-of-stay as was once thought [91][92][93][94][95]. The practices most consistently associated with earlier extubation and/or lower mortality rates are those focused on limiting exposure to invasive mechanical ventilation by avoiding intubation and speeding extubation [96].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
“…There is no association between oral care with chlorhexidine and lower VAP rates on meta-analysis of double-blind randomized trials [99]. More concerningly, some meta-analyses and observational studies have reported that oral care with chlorhexidine may increase mortality rates, perhaps because some patients may aspirate some of the antiseptic triggering acute lung injury [91,95,99,100,111,112]. A cluster randomized de-adoption study is currently underway to better characterize the safety and effectiveness of oral chlorhexidine for ventilated patients [113].…”
Section: In Intubated Patients Suspected Of Having Vap Should Distalmentioning
confidence: 99%
“…; (2) repeated oral temperatures >99°F; or (3) an increased temperature >2°F above baseline. 4 This is important because older adults incur high risks of influenza-associated complications, 5 and 2017 NHSN criteria define fever exclusively as temperature >100.4°F.…”
mentioning
confidence: 99%
“…Our proposed modified definition had criteria identical to those of the 2017 NHSN definition except for fever, which was defined according to the IDSA guidelines for older adults ≥65 years of age. 4 For all patients, we recorded demographics, comorbidities, antiviral therapy, receipt of seasonal influenza vaccine, hospital characteristics, all-cause mortality, and whether NHSN criteria were present. Influenza infection was categorized as communityacquired versus hospital-acquired based on detection within 48 hours of admission.…”
mentioning
confidence: 99%
“…Oral care with chlorhexidine has come under scrutiny in recent years because of a series of studies associating oral chlorhexidine with a possible increased risk of mortality and ventilator-associated events. 84 This signal has been noted on meta-analyses of randomized trials, 73,85 observational analyses of associations between ventilator bundle components and outcomes, 31,86,87 and in one hospital-wide observational analysis of prescribed medications. 88 In addition, doubt has been cast on whether oral care with chlorhexidine truly prevents VAP.…”
Section: Oral Care With Chlorhexidinementioning
confidence: 97%